WACANA SIRKUMSISI PADA PEREMPUAN - Akhmad Rifa'i (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2001)
There are two perspectives of female circumcision among scholars. First, female circumcision is a matter of tradition that has been legalized by religious interpretations, especially Islam. Essentially, Islam does not obligate women to practice it. The practice could be accepted as far as it doesn't not destroy the functions of woman sex organ. Second, female circumcision is a tradition that has been legalized by men powers for satisfying themselves in sexual performance as well as in social relations. Female genital mutilation, which means removing the clitoris, labia minora and majora of the female sex organ, is the practice to make males having more pleasure in sexual relationship. Here, the objective of such practice is to insult 'female dignity' and to show that females should obey males domination. Islam prohibits the latter practice.